Adhesively bonded CFRP/Al joints: Influence of the surface pretreatment on corrosion during salt spray test. Issue 2 (18th October 2021) - Schanz, Jochen; Nester, Sara; Meinhard, Dieter; Pott, Timo; Riegel, Harald; De Silva, Anjali K. M.; Harrison, David K.; Knoblauch, Volker
Abstract: The objective of this study was to investigate the influence of different surface pretreatments on the aging behavior of adhesively bonded carbon fiber reinforced polymers/Al joints in a standardized salt spray environment. Therefore, the bonding surfaces were acetone‐cleaned or laser‐pretreated by near‐infrared laser radiation. The pretreated surfaces were examined using optical microscopes, roughness measurements, and infiltration tests. Mechanical testing of the joints was performed in the unaged state and after five aging durations from 120 to 1440 h. The acetone‐cleaned specimens lose a maximum 20% of their initial average shear strength of 22 MPa after aging up to 1440 h. In contrast, the fracture patterns of the laser‐pretreated samples show corrosive degradation after 720 h, indicating galvanic coupling and crevice corrosion. This leads to a significant decrease in shear strength up to 50% after 1440 h of aging. Therefore, some strategies to avoid contact corrosion via the pretreatment and joining process are presented additionally. Abstract : The influence of acetone and laser surface pretreatments on the corrosion behavior of CFRP/Al‐bonds has been investigated. The laser pretreatment exposes the carbon fibers and generates a linear‐structured aluminum surface. The resulting contact between the dissimilar materials leads to galvanic corrosion in the salt spray test. Therefore, the mechanical strength of these specimens is reduced significantly compared to the acetone‐cleaned joints.